Variations in phytosanitary and other management practices in Australian grapevine nurseries - WAITE, Helen; MAY, Peter; BOSSINGER, Gerd (Phytopathologia Mediterranea, 2013)
Sporadic and costly failure of newly planted vines is an ongoing problem in the Australian wine industry. Failed vines are frequently infected with wood pathogens, including the fungi associated with Young Vine Decline. Hot water treatment (HWT) and other nursery practices have also been implicated in vine failure. We undertook a survey of Australian grapevine nurseries to develop an understanding of current propagation practices and to facilitate the development of reliable propagation procedures that consistently produce high quality vines. A survey covering all aspects of grapevine propagation including sources of cuttings, HWT, sanitation and cold storage was mailed to all 60 trading Australian vine nurseries. In all, 25 nurseries responded, a response rate of 41.7%. Practices were found to vary widely both within and between nurseries. The vast majority of respondents (20) reported that they currently used, or had used, HWT, but the reliability of HWT was questioned by most nursery operators. A majority (18) felt that some Vitis vinifera varieties were more sensitive to HWT than others. Hydration also emerged as an important factor that had the potential to affect vine quality. All respondents used hydration and although the majority used treated water, cuttings were not generally seen as a source of cross contamination. Our study identified a clear need for further research into the effects of HWT on cutting physiology and the role of hydration in the epidemiology of grapevine pathogens, and the importance of incorporating the results of such research into practical and comprehensive propagation guidelines for vine nurseries.